2016
DOI: 10.2337/db16-0213
|View full text |Cite
|
Sign up to set email alerts
|

Lipodystrophy Due to Adipose Tissue–Specific Insulin Receptor Knockout Results in Progressive NAFLD

Abstract: Ectopic lipid accumulation in the liver is an almost universal feature of human and rodent models of generalized lipodystrophy and is also a common feature of type 2 diabetes, obesity, and metabolic syndrome. Here we explore the progression of fatty liver disease using a mouse model of lipodystrophy created by a fat-specific knockout of the insulin receptor (F-IRKO) or both IR and insulin-like growth factor 1 receptor (F-IR/IGFRKO). These mice develop severe lipodystrophy, diabetes, hyperlipidemia, and fatty l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 44 publications
6
96
0
3
Order By: Relevance
“…The importance of visceral adipose tissue as site of chronic inflammation is further supported by some studies demonstrating that the lack of adipocyte 5′ AMP-activated protein kinase worsens insulin resistance and liver disease by affecting brown and beige adipose tissue function 163. Additionally, adipose tissue-specific insulin receptor knockout mice develop more severe NAFLD with histological evidence of ballooning degeneration further supporting the notion that the adipose tissue is of key importance in the development and progression of NAFLD 164. In contrast, recent research has found that adipose tissue type I interferon signalling may protect from metabolic dysfunction 165…”
Section: Putative Mechanisms Linking Nafld To Extrahepatic Conditionsmentioning
confidence: 84%
“…The importance of visceral adipose tissue as site of chronic inflammation is further supported by some studies demonstrating that the lack of adipocyte 5′ AMP-activated protein kinase worsens insulin resistance and liver disease by affecting brown and beige adipose tissue function 163. Additionally, adipose tissue-specific insulin receptor knockout mice develop more severe NAFLD with histological evidence of ballooning degeneration further supporting the notion that the adipose tissue is of key importance in the development and progression of NAFLD 164. In contrast, recent research has found that adipose tissue type I interferon signalling may protect from metabolic dysfunction 165…”
Section: Putative Mechanisms Linking Nafld To Extrahepatic Conditionsmentioning
confidence: 84%
“…Tissues were stored frozen or fixed in formalin, and sections were stained with H&E. Liver histology was graded by a board-certified veterinary pathologist blinded to the experimental conditions, and NAS was assessed as previously published (27). Triglycerides from liver samples were measured according to previously published methods (63). In brief, 100 mg of liver tissue was homogenized in 1 ml of chloroformmethanol (2:1 v/v).…”
mentioning
confidence: 99%
“…Genetic mouse models of lipodystrophy develop markedly depleted adipose stores, severe fatty liver disease and systemic insulin resistance (Saha et al 2004, Softic et al 2016. Due to limited adipose tissue lipid storage, patients with lipodystrophy frequently develop NAFLD and are at an increased risk for developing hypertriglyceridemia 234:1 and diabetes (Safar Zadeh et al 2013, Akinci et al 2015.…”
Section: Adipose Tissue Lipolysis and Hepatic Lipid Uptakementioning
confidence: 99%